Prosthetic Rehabilitation of a Patient after Hemimaxillectomy due to Squamous Cell Carcinoma in the Maxillary Sinus: Case Report - Emam, AbdelNaser Mohammed (European Journal of General Dentistry, 2024)
Rehabilitation of uncontrolled diabetics with impairments due to acquired defects is complex. More significant defects are more challenging to treat than smaller ones, which can often be corrected surgically. When surgical reconstruction is not possible, the preferred treatment method for facial defects is prosthetic reconstruction. An obturator prosthesis is a standard and efficient method for treating such maxillary defects. This case report aims to evaluate patients' satisfaction with uncontrolled diabetes with improved speech, swallowing, and articulation, and achieving acceptable aesthetics after rehabilitation.This case report details the ultimate obturator prosthesis therapy for an elderly male patient who had a hemimaxillectomy because of squamous cell cancer of the maxillary air sinus. The patient had uncontrolled diabetes and mobility grade 1 of the remaining upper teeth. A gauze coated with Vaseline blocked a significant medial undercut in the defect. The primary, final impression, and jaw relationships were recorded to aid postoperative speech and deglutition. Normal palatal contours were replicated to ensure functional outcomes. The obturator portion was hollowed to reduce its weight and prevent unnecessary strain on the supporting teeth and tissues. The obturator was fabricated using heat-cured acrylic resin to allow future additions in the event of tooth extraction and relining.A well-made and constructed obturator for diabetic patients can offer high adaptability and functionality. Multidisciplinary planning is essential for effective dental care and functional rehabilitation, and avoiding oroantral communication. This will significantly improve the patient's quality of life.
Keywords: maxillofacial defect; hemimaxillectomy; interim obturator; maxillofacial prosthesis; prosthetic rehabilitation